A concept study for cost effective NGH mid-stream supply chain establishing strategies. (1st February 2016) - Kang, Hee Jin; Yang, Youngsoon; Ki, Min Seok; Shin, Myung Soo; Choi, Jin; Cha, Jong-Ho; Lee, Dongkon
Abstract: To date, small and midsized gas fields remain undeveloped due to economic issues. Recently, however, natural gas hydrate (NGH) has become expected to be more affordable than liquefied natural gas (LNG) in terms of the cost of establishing a supply chain over a certain range of transport distances from gas-fields and natural gas deposits. However, it is difficult to realize the economic benefit of NGH compared with LNG because the energy storage efficiency of NGH is relatively low. Therefore, the economic feasibility of concept designs for NGH pellet (NGHP) carriers should be evaluated before their commercialization. Other design alternatives should also be studied for additional cost reduction. In this paper, an NGH tank container is studied as a design alternative for cost-effective mid-stream supply chain establishment. For economic feasibility, the utilization of existing container ships, wharfs and other facilities is considered. Special attention is given to shortening long layovers and simplifying the regasification process. Because many small and midsized gas fields are distributed on the coast, the cost comparison assumes that natural gas is gathered to the land basis platform using a pipeline and is then formatted and pelletized for mass marine transportation. Highlights: Economic feasibility is important for small to medium gas field development. Existing technical issues of the NGH pellet carrier are reviewed. Requirements are analyzed for the cost-effective mid-stream NGH supply chain establishing. On the basis of the requirements analysis result, NGH tank container has been proposed. The proposed NGH tank container is expected to reduce the capital cost of mid-stream supply chain.